Fasilitasi Peringatan Hari Santri Nasional Kabupaten Wonosobo - Ngatoillah Linnaja; Muhammad Saefullah; Robingun Suyud El Syam; Salis Irvan Fuadi (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This article presents the results of research regarding facilitation to commemorate National Santri Day in Wonosobo Regency. The mentoring stage is carried out through three steps, namely: planning, implementation and evaluation. The activities take the form of field research with data collection through observation, interviews and documentation, then descriptive analysis. The results of this research show that accompanying the commemoration of National Santri Day in Wonosobo Regency to the santri can raise awareness of heroic values in everyday life. This also provides an understanding of the importance of commemorating National Santri Day, by loving ulama, and being ready to fight in various fields to advance the nation.